Analysis of E-Commerce and Fintech Applications in Promoting UMKM Development in Padangsidempuan - Haryanti, Nadya; Nurbaiti, Nurbaiti; Ikhsan Harahap, Muhammad (Universitas Ibn Khladun Bogor, 2023)
The purpose of this research is to see the development of Fintech technology and E-Commerce for UMKM in Padangsidimpuan city. The development of financial technology in Padangsidimpuan City is increasing, but there are still many people in Padangsidimpuan City who have not been served and use information technology. This study uses a qualitative approach with the types of data used by this study are primary and secondary data. Primary data, obtained based on interviews with respondents or informants. While secondary data obtained from journal literature, data, news, surveys, reports and theories related to research problems. This study uses analysis seen from the IFAS and EFAS matrices obtained from informants who are MSMEs in Padangsidimpuan City. The results of the study show that an aggressive strategy is the right strategy in encouraging the development of UMKM in Padangsidimpuan City to continue to maximize the strengths and opportunities that exist. From the results of the interviews, technological developments have not completely affected the SMEs of Padangsidimpuan City, because some of them are still attached to traditional culture. However, some of the UMKM in Padangsidimpuan City have used Fintech and E-Commerce services in their companies.